2019
DOI: 10.1101/831719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic bases of grafting-induced vigour in eggplant

Abstract: 27In horticulture, grafting is a popular technique used to combine positive traits from two different plants. This 28 is achieved by joining the plant top part (scion) onto a rootstock which contains the stem and roots. Despite its 29 wide use, the biological mechanisms driving rootstock-induced alterations of the scion phenotype remain 30 largely unknown. Given that epigenetics plays a crucial role during distance signalling in plants, we studied 31 the genome-wide changes induced by DNA methylation in eggpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…According to the obtained results in the present study, although the methylation levels in CG were highest throughout genome, the methylation changes in CHG and CHH were more frequent. The similar results were also reported previously [15,30,42]. Apart from the significant decrease in CHH methylation found in grafted eggplants [15], CHH methylation was reported to change significantly and the CHH-DMRs account for most of the DMRs during the developmental processes of soybean seeds [30].…”
Section: Methylation Alterations Induced By Grating With Different Ro...supporting
confidence: 89%
See 3 more Smart Citations
“…According to the obtained results in the present study, although the methylation levels in CG were highest throughout genome, the methylation changes in CHG and CHH were more frequent. The similar results were also reported previously [15,30,42]. Apart from the significant decrease in CHH methylation found in grafted eggplants [15], CHH methylation was reported to change significantly and the CHH-DMRs account for most of the DMRs during the developmental processes of soybean seeds [30].…”
Section: Methylation Alterations Induced By Grating With Different Ro...supporting
confidence: 89%
“…The similar results were also reported previously [15,30,42]. Apart from the significant decrease in CHH methylation found in grafted eggplants [15], CHH methylation was reported to change significantly and the CHH-DMRs account for most of the DMRs during the developmental processes of soybean seeds [30]. Domb et al also found that specific elimination of CG methylation did not dysregulate genes or transposons, and, in contrast, exclusive removal of non-CG methylation massively up-regulated genes and transposons [42].…”
Section: Methylation Alterations Induced By Grating With Different Ro...supporting
confidence: 83%
See 2 more Smart Citations
“…The translocation of siRNAs across the grafting junction has also been explored in several crops, including eggplant, pumpkin (Cucurbita pepo), cucumber, potato, Nicotiana benthamiana, grapevine (Vitis vinifera) and several bean (Fabaceae) species (Tournier et al, 2006;Bai et al, 2011;Zhang et al, 2014;Cerruti et al, 2021;Davoudi et al, 2022;Rubio et al, 2022;Zhang et al, 2022). In addition, several miRNAs in potato have been demonstrated to be graft-transmissible, including miR156, miR339, miR395 and miR172 (Pant et al, 2008;Buhtz et al, 2010;Kasai et al, 2010).…”
Section: Movement Of Small Non-coding Rna Moleculesmentioning
confidence: 99%